Collecting qualitative data using a smartphone app: Learning from research involving people with experience of multiple disadvantage. Issue 3 (November 2022) - Welford, Joanna; Sandhu, Jatinder; Collinson, Beth; Blatchford, Sheila
This article discusses the use of a smartphone application ('app') as a method for undertaking diary-based qualitative research with a group of participants with lived experience of multiple disadvantage (experience of two or more of homelessness, offending, mental ill-health and substance misuse). As part of a multi-method approach to the study, an app was designed for participants to capture rich, real-time qualitative data through a variety of media – text, audio, image and video – to make it accessible and interactive for participants. There is an identified gap in the use of apps to collect qualitative data with marginalised groups, and this paper reflects on our experience of designing and implementing an app as part of a wider multi-method research project. We argue that, particularly during the challenges of adapting research methods in light of the COVID-19 pandemic, the smartphone app has considerable potential for engaging participants in a flexible way to involve marginalised groups. Qualitative researchers in particular should consider the potential of this approach, and encourage others to share their reflections and learning.